Horticulture and its relation to agriculture - Snyder, Carl (My University, 1896)
Introduction: By the majority of the reading public and especially the farming class the word Horticulture has a very peculiar meaning. When one speaks of Horticulture to an ordinary farmer he immediately thinks of a large amount of money to be spent, years of toil and so far as he can see no pay for his hard days work. But by looking over the history of various industries I find that Horticulture is as old if not older than Agriculture.
Citation: Snyder, Carl. Horticulture and its relation to agriculture. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Horticulture; Agriculture; Farmer; Theses; Manuscripts (documents)